2020
DOI: 10.3390/su122410536
|View full text |Cite
|
Sign up to set email alerts
|

Research on the International Roughness Index Threshold of Road Rehabilitation in Metropolitan Areas: A Case Study in Taipei City

Abstract: The International Roughness Index (IRI) is the standard scale for evaluating road roughness in many countries in the world. The Taipei City government actively promotes a Road Smoothing Project and plans to complete the rehabilitation of the main and minor roads within its jurisdiction. This study aims to detect the road surface roughness in Taipei City and recommend appropriate IRI thresholds for road rehabilitation. A total of 171 asphalt concrete pavement sections in Taipei City with a total length of 803.4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In [21], the spaceborne L-band ALOS-PALSAR datasets with 7 m spatial resolution were used to map the relationship between the SAR backscatter values and the international roughness index (IRI) values of the roads in Thailand. The IRI is a widely used parameter to indicate the unevenness of the road surface [22]. A similar study can be found in [23], where the spaceborne X-band Cosmo-SkyMed SAR datasets with 3 m spatial resolution were used to derive the IRI of the roads in the Commonwealth of Virginia, USA.…”
Section: Introductionmentioning
confidence: 77%
“…In [21], the spaceborne L-band ALOS-PALSAR datasets with 7 m spatial resolution were used to map the relationship between the SAR backscatter values and the international roughness index (IRI) values of the roads in Thailand. The IRI is a widely used parameter to indicate the unevenness of the road surface [22]. A similar study can be found in [23], where the spaceborne X-band Cosmo-SkyMed SAR datasets with 3 m spatial resolution were used to derive the IRI of the roads in the Commonwealth of Virginia, USA.…”
Section: Introductionmentioning
confidence: 77%
“…It is defined as "the accumulated suspension vertical motion divided by the distance traveled as obtained from a mathematical model of a simulated quarter-car traversing a measured profile at 80 km/h" [25]. This index is the basic tool for assessing the quality of the pavement after construction, during use and after modernization [26][27][28][29][30]. The guidelines for calculating the IRI are described in the documents [31,32].…”
Section: Measurement Methods Used To Assess Mining Influencesmentioning
confidence: 99%
“…Some of the most commonly used indicators for measuring pavement roughness include the International Roughness Index (IRI), Profile Index (PI), Maysmeter Index (MI), Root mean Square Vertical acceleration (RMSVA), y Ride Number (RN), etc. (Chen et al, 2020). The most internationally used method is the IRI, which was developed by the World Bank during the "International Road Roughness Experiment" (IRRE) carried out in Brazil in 1982 (Sayers et al, 1986).…”
Section: Proposed Bymentioning
confidence: 99%
“…The most internationally used method is the IRI, which was developed by the World Bank during the "International Road Roughness Experiment" (IRRE) carried out in Brazil in 1982 (Sayers et al, 1986). The IRI is a mathematical model that simulates the suspension and mass of a typical vehicle traveling along a stretch of road at a reference speed, typically 80 km/h (50 mph) (Bridgelall et al, 2016), (Chen et al, 2020). This model is known as "Quater Car Simulation" (QCS) since it represents the quarter of a four-wheeled vehicle.…”
Section: Proposed Bymentioning
confidence: 99%